2003
DOI: 10.1124/dmd.31.7.932
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism-Based Inactivation of Neuronal Nitric-Oxide Synthase by Components of Cigarette and Cigarette Smoke

Abstract: This article is available online at http://dmd.aspetjournals.org ABSTRACT:It has been shown that administration of cigarette smoke to rats leads to loss of neuronal nitric-oxide synthase (nNOS) activity and nNOS protein in penile tissue. The exact mechanism for this loss of activity and protein is not known. In the current study, we investigated whether extracts prepared from cigarette smoke or from the cigarette itself could directly inhibit nNOS activity. We discovered that the cigarette smoke extract and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 29 publications
2
22
0
Order By: Relevance
“…Our findings in regard to the direct actions of CSE on NOS enzymatic activity are consistent with studies that predict that the catalytic domain of human eNOS contains 10 cysteine residues with 2 of them (Cys-94 and Cys-99) being responsible for coordinating an intermolecular interaction between 2 monomers. 35 Although our observations are also consistent with previous reports, 13,[22][23][24] some longer-term studies 13,[22][23][24] suggest that a reduction in NOS activity parallels to some extent a decrease in eNOS content. In our study, we saw a more rapid onset of the inhibitory effect of CSE on NOS activity, using isolated purified eNOS enzyme.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Our findings in regard to the direct actions of CSE on NOS enzymatic activity are consistent with studies that predict that the catalytic domain of human eNOS contains 10 cysteine residues with 2 of them (Cys-94 and Cys-99) being responsible for coordinating an intermolecular interaction between 2 monomers. 35 Although our observations are also consistent with previous reports, 13,[22][23][24] some longer-term studies 13,[22][23][24] suggest that a reduction in NOS activity parallels to some extent a decrease in eNOS content. In our study, we saw a more rapid onset of the inhibitory effect of CSE on NOS activity, using isolated purified eNOS enzyme.…”
Section: Discussionsupporting
confidence: 82%
“…Previous studies suggest that the effect of CSE may relate in part because of reduced NOS expression and enzymatic activity. 13,[22][23][24] Alternatively, Hutchison et al 5 showed previously that arginine supplementation attenuated the endothelial dysfunction caused by exposure to cigarette smoke, suggesting that substrate availability for NOS may be a key mechanism for CSE-induced endothelial dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Smoking was reported to inhibit endothelial and neuronal NO synthases, impair NO signaling due to increased release of superoxide anion and subsequent inactivation of nitric oxide, and reduce exhaled NO in man, which is an indicator of decreased endogenous NO production (Raij et al, 2001;Demady et al, 2003;Landmesser, Harrison & Drexler, 2005). Inhibition of neuronal or endothelial nitric oxide synthase was shown to attenuate the stimulus evoked flow response in different animal studies, indicating the substantial role of NO in the coupling of neuronal activation to regional cerebral blood flow (Kharitonov, Robbins, Yates, Keatings & Barnes, 1995;Cholet, Seylaz, Lacombe & Bonvento, 1997;Yang & Iadecola, 1998;Demady et al, 2003). Dysregulation of Ca 2+ -channels was also demonstrated in nicotine treated animals, mimicking the effect of an apparent decrease in bioavailability of endogenous NO (Gerzanich, Zhang, West & Simard, 2001).…”
Section: Possible Causes Of Impaired Vasodilation In Chronic Smokersmentioning
confidence: 99%
“…Tobacco extract concentrate was prepared from nicotinefree Quest Cigarettes (Vector Tobacco Inc., Timberlake, NC) as described by Demady et al, 9 and was produced every 10 days to maintain freshness. Tobacco from four cigarettes was ground, mixed with 40 ml of distilled water, then filtered and centrifuged at 5,000 rpm for 20 min.…”
Section: Methodsmentioning
confidence: 99%